Digital Transformation of Teacher Leadership: Innovative Strategies for Increase Quality of Primary and Secondary Education - Surohmat, Dedi Slamet; Firdaus, Rangga (STKIP Al Islam Tunas Bangsa dan HEPI, 2025)
Teacher leadership development is a strategic element in improving the quality of education, especially at the primary and secondary school levels. Along with the rapid digital transformation, technology-based training emerges as an innovative alternative to strengthen teachers' professional competencies on an ongoing basis. This study aims to assess the effectiveness of Android-based digital training media in improving teacher leadership skills, including aspects of classroom management, effective communication, and student motivation. The method used was mixed method with ADDIE development model, involving 100 teachers (experimental and control groups) and qualitative data through interviews and observations. Quantitative results showed a significant improvement in all three aspects of leadership skills after the training, with significant differences between the experimental and control groups (p < 0.05). Specifically, there was a 25% increase in classroom management, 30% increase in effective communication, and 28% increase in student motivation in the experimental group compared to the control group. Qualitative results supported these findings, with teachers reporting positive changes in classroom management practices and interactions with students. These findings confirm that Android-based digital training is effective in shaping teacher leadership that is adaptive, communicative, and responsive to 21st century learning needs. The integration of digital training is recommended as a strategy in teachers' continuous professional development programs.